Retrospective analysis of scleritis or peripheral ulcerative keratitis in systemic vasculitis: insights from a single tertiary centre - Lucy Hong; Rona Smith; Rachel Jones; David Jayne; Erika Damato; Kevin Loudon (Clinical Medicine, 2025)
Introduction: Ocular manifestations of systemic vasculitis are rare and often difficult to treat, resulting in increased morbidity for affected patients. Comprehensive epidemiological and clinical data on the natural history of ocular vasculitis remain limited, hindering effective management and understanding of these conditions. Materials and Methods: To address this gap, we conducted a retrospective analysis of 154 patients who presented to a tertiary vasculitis service between October 2014 and July 2024 with scleritis or peripheral ulcerative keratitis (PUK) associated with systemic vasculitis. Patients without clinical or serological evidence of systemic disease were excluded, and all diagnoses were confirmed by a medical ophthalmologist. Our analysis examined demographic characteristics, prevalence of vasculitis subtypes, and treatment regimens. Results and Discussion: Women (2:1) and individuals aged 50–79 years were more frequently affected by ocular vasculitis. Anti-neutrophil cytoplasmic antibody (ANCA) vasculitis was the most common underlying condition (36.7%), followed by rheumatoid arthritis (31.3%), systemic lupus erythematosus (4%) and relapsing polychondritis (4%). Among ANCA vasculitis patients with scleritis (n=42), PR3 positivity was predominant (75.6%), whereas PUK cases (n=11) exhibited a more balanced PR3 (54.5%) and MPO (45.5%) distribution.Of the 53 patients with ANCA vasculitis, 67.9% had ocular involvement at initial presentation, with scleritis (54.7%) being more common than PUK (13.2%). The remaining 32.1% developed ocular involvement during relapse. Among those with ocular symptoms at onset (n=36), 27.8% had isolated ocular disease (16.7% scleritis, 11.1% PUK), while 72.2% had concurrent systemic involvement. Notably, scleritis was frequently associated with non-organ-threatening systemic symptoms (eg, ear nose throat, non-ulcerating skin disease, myositis, joint or non-cavitating lung disease).Cyclophosphamide was the primary induction agent for ocular involvement in ANCA vasculitis (40.0%), but was replaced by rituximab on relapse (59.2%). Steroids were frequently used with both cyclophosphamide and rituximab, alongside other immunosuppressants, including mycophenolate mofetil, methotrexate and azathioprine. Among ANCA vasculitis patients without initial ocular involvement, cyclophosphamide remained the most used induction agent (50.0%), while rituximab was the preferred relapse therapy (64.7%). Conclusion: These findings underscore the need for increased awareness and targeted research into ocular vasculitis. The distinct relapse patterns and treatment responses highlight the importance of multidisciplinary care integrating both systemic and ophthalmological expertise. Establishing dedicated ocular vasculitis services could improve disease monitoring, treatment outcomes and overall patient care.